Effect of risk messages on risk appraisals, attitudes, ambivalence, and willingness to smoke hookah in young adults. Issue 1 (1st January 2020) - Mays, Darren; Johnson, Andrea C.; Phan, Lilianna; Tercyak, Kenneth P.; Rehberg, Kathryn; Lipkus, Isaac
ABSTRACT: Objective: We examined effects of hookah tobacco risk messages on risk appraisals, attitudes towards hookah, ambivalence about hookah use, and willingness to smoke in young adults aged 18–30 years ( n = 234). Design: In an online experiment, participants completed pre-exposure measures and were randomized to hookah tobacco risk messages or to a no message control condition. Main Outcome Measures: Risk appraisals, attitudes, ambivalence, and willingness to smoke hookah. Results: Those who viewed risk messages reported greater risk appraisals (M 4.50, SD 1.17 vs. M 3.87, SD 1.16, p < .001), less positive attitudes (M −0.56, SD 1.24, vs. M 0.39, SD 1.35, p < .001), greater ambivalence (M 3.86, SD 1.26, vs. M 3.08, SD 1.32, p < .001), and less willingness to smoke than controls (M 4.48, SD 1.27, vs. M 4.85, SD 1.37, p = .034). Structural equation modeling demonstrated messages reduced willingness to smoke by evoking less positive attitudes ( b = −0.15, 95% CI −0.32, −0.05) and by the effect of heightened risk appraisals on less positive attitudes ( b = −0.14, 95% CI −0.30, −0.07). Conclusions: Honing messages and understanding their mechanisms of action are necessary to produce more effective interventions to address hookah and other tobacco use in young adults.